2018
DOI: 10.1074/jbc.ra118.003153
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-activated Cl− currents in the murine vomeronasal organ enhance neuronal spiking but are dispensable for male–male aggression

Abstract: Ca-activated Cl currents have been observed in many physiological processes, including sensory transduction in mammalian olfaction. The olfactory vomeronasal (or Jacobson's) organ (VNO) detects molecular cues originating from animals of the same species or from predators. It then triggers innate behaviors such as aggression, mating, or flight. In the VNO, Ca-activated Cl channels (CaCCs) are thought to amplify the initial pheromone-evoked receptor potential by mediating a depolarizing Cl efflux. Here, we confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 64 publications
(110 reference statements)
1
19
0
Order By: Relevance
“…Specifically, conditional knockout of TMEM16A/ANO1 abolished the Ca 2+ -activated Cl − currents in mature VSNs, establishing ANO1 as the primary mediator of this transduction current ( Amjad et al 2015 ). This finding was recently confirmed in VSN recordings from ANO1/2 conditional double knockout mice, which show diminished spontaneous and pheromone-evoked action potential firing ( Münch et al 2018 ). It therefore came as a surprise that these double knockout mice did not display profound changes in resident–intruder paradigm-induced male territorial aggression ( Münch et al 2018 ).…”
Section: Vsn Transductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Specifically, conditional knockout of TMEM16A/ANO1 abolished the Ca 2+ -activated Cl − currents in mature VSNs, establishing ANO1 as the primary mediator of this transduction current ( Amjad et al 2015 ). This finding was recently confirmed in VSN recordings from ANO1/2 conditional double knockout mice, which show diminished spontaneous and pheromone-evoked action potential firing ( Münch et al 2018 ). It therefore came as a surprise that these double knockout mice did not display profound changes in resident–intruder paradigm-induced male territorial aggression ( Münch et al 2018 ).…”
Section: Vsn Transductionmentioning
confidence: 55%
“…This finding was recently confirmed in VSN recordings from ANO1/2 conditional double knockout mice, which show diminished spontaneous and pheromone-evoked action potential firing ( Münch et al 2018 ). It therefore came as a surprise that these double knockout mice did not display profound changes in resident–intruder paradigm-induced male territorial aggression ( Münch et al 2018 ).…”
Section: Vsn Transductionmentioning
confidence: 55%
See 1 more Smart Citation
“…While OBPs binding to odors is well-documented at the biochemical level, very few investigations into OR binding have been reported. Activation of ORs with odorant molecules alone, with OBP bound or unbound to odorants, have been measured by electrophysiology [e.g., (4)] or other indirect techniques [e.g., (5, 6)]. This lack of direct evidence explains why the nature of ORs ligands is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…4 c). Interruption of the signaling pathways can severely dampen animals’ behavioral responses, including food seeking, sex identification and preference, and aggression 21 , 22 . Previous studies have shown that abolishment of either Gαi2, Gαo or Gγ8 expression in the VNO abrogated the male–male aggression 17 , 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%